AI*IA 2013: Advances in Artificial Intelligence XIIIth International Conference of the Italian Association for Artificial Intelligence, Turin, Italy, December 4-6, 2013, Proceedings - Baldoni, Matteo; Baroglio, Cristina; Boella, Guido; Micalizio, Roberto (Lecture Notes in Artificial Intelligence, 2013)
This book constitutes the refereed proceedings of the 13th International Conference of the Italian Association for Artificial Intelligence, AI*IA 2013, held in Turin, Italy, in December 2013. The 45 revised full papers were carefully reviewed and selected from 86 submissions. The conference covers broadly the many aspects of theoretical and applied Artificial Intelligence as follows: knowledge representation and reasoning, machine learning, natural language processing, planning, distributed AI: robotics and MAS, recommender systems and semantic Web, and AI applications.